Advanced power plant materials, design and technology - Roddy, Dermot (Woodhead Publishing in energy, 2010)
This book initially reviews improved plant designs for efficiency and fuel flexibility, including combined-cycle technology and utilisation of lower-grade feedstocks. Coverage extends to advanced material and component use, and the incorporation of alternative energy conversion technology, such as hydrogen production.